Pendekatan Grounded Theory untuk Memahami Strategi Pemerintah Daerah Istimewa Yogyakarta dalam Menghadapi Era Otonomi Daerah dan Globalisasi - Fathul Himam; Bagus Riyono; Sumaryono Sumaryono (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2004)
This grounded theory research approach was directed to understand how Pemerintah Daerah developed its strategic process in dealing with local autonomy and globalization, both on the organizational level and individual level. In-depth interview was applied to 14 high level Pemerintah Daerah Officials. It was directed to understand their experiences in managing changing situations. The results showed that there were six major themes: (1) empowering the society; (2) restructuring the organization; (3) improving management system; (4) economic development; (5) developing the human resources; and (6) shifting the mindset. Reanalyzing these themes by using selective and axial coding, it was found that there were two emerging major functions of the strategy, i.e.(1) Maintaining the system; (2) adapting to environmental demands.Keywords: grounded theory, open coding, selective coding, axial coding, themes, strategy.